2021
DOI: 10.21037/tlcr-20-1281
|View full text |Cite
|
Sign up to set email alerts
|

Watershed analysis of the target pulmonary artery for real-time localization of non-palpable pulmonary nodules

Abstract: Background: Some pulmonary nodules are not suitable for computed tomography-guided percutaneous localization. This study aimed to investigate the feasibility and safety of real-time localization for these nonpalpable pulmonary nodules using watershed analysis of the target pulmonary artery during thoracoscopic wedge resection.Methods: Watershed analysis is a novel technique that can be used to create a specific area on the lung surface for nodule localization. This analysis is performed by temporarily blocking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, repeated angiographies can be performed and may be helpful; otherwise, intraoperative clamping of the pulmonary lobar veins may enable prolongation of washout time ( 32 ). In addition, previous literature reports have demonstrated that ICG-guided watershed analysis of the target pulmonary artery for nodule localization is safe and effective, especially in selected patients undergoing thoracoscopic wedge resection, which may be a feasible and attractive alternative method for localizing non-palpable pulmonary nodules ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, repeated angiographies can be performed and may be helpful; otherwise, intraoperative clamping of the pulmonary lobar veins may enable prolongation of washout time ( 32 ). In addition, previous literature reports have demonstrated that ICG-guided watershed analysis of the target pulmonary artery for nodule localization is safe and effective, especially in selected patients undergoing thoracoscopic wedge resection, which may be a feasible and attractive alternative method for localizing non-palpable pulmonary nodules ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, professors Chu XP and Zhong WZ mentioned a similar approach, which involves temporarily blocking the target pulmonary artery and using indocyanine green fluorescence during surgery. 17) We believe that there are two differences. First, in addition to blocking the pulmonary arteries, we can also choose to block target veins in individual cases.…”
Section: Discussionmentioning
confidence: 97%
“…A watershed method is one of the most frequent segmentation algorithms used in the processing of medical [35] and material science images [36]. It is built on the depiction of a grayscale image as a flooded topographic relief, with watersheds delineating regions of water from various basins [37]. The traditional watershed [38] is designed around flood modelling.…”
Section: Segmentationmentioning
confidence: 99%